DEMOCRACY DIALOGUE: THE SUSTAINABILITY OF DEMOCRACY IN SOUTHEAST ASIA - CASE STUDY ON THE INDONESIAN PRESIDENTIAL ELECTION - Novianty Djafri; Caroline; Sitti Nur Alam; Erfan Hasmin; Zulvia Trinova (ADISAM Publisher, 2024)
This research paper examines the sustainability of democracy in Southeast Asia, focusing on Indonesia's Presidential Election as a case study. The region's diverse political landscape has undergone significant transformations influenced by globalization, civil society movements, and international pressures. As the largest country in Southeast Asia, Indonesia is a crucial example of a nation transitioning from authoritarian rule to democracy. Through qualitative and quantitative research methods, the study analyzes key variables influencing Indonesian democracy, such as democratic institutions, civil society participation, political parties, decentralization, socioeconomic factors, ethnic diversity, and international relations. Findings highlight the complex interactions of these variables in shaping the sustainability of democracy in Indonesia and offer broader implications for the region. While progress has been made in democratic consolidation, political instability and corruption persist. Understanding the complexities of democracy in Southeast Asia provides valuable insights for policymakers and advocates, emphasizing the need for continued dialogue and cooperation to promote sustainable democratic practices and foster regional stability and development.